Subjective Assessment of Croatian Dental Medicine Students on Their Knowledge and Skills in Prosthodontics - Nikša Dulčić; Vlaho Brailo; Valentina Rezo; Marina Katavić; Vedran Sablić; Ivica Pelivan (University of Zagreb. School of Dental Medicine, 2017)
Objectives: The aim of the study was to establish the subjective perception of dental medicine students' knowledge and skills in prosthodontics and to determine both how their perception changed during their study, by gaining clinical experience. Also, the aim was to investigate if there were any socio-demographic factors that influenced students' perception. Methods: The research, based on an anonymous survey for dental medicine students was carried out at the School of Dental Medicine, University of Zagreb in 2015. YES/NO/DO NOT KNOW questions were used for assessment of students' knowledge, and a 50 mm visual analog scale was used for assessment of their abilities and skills. The Chi-square test, t-test for independent samples, analysis of variance and the Pearson's correlation coefficient were used for statistical data analysis. Results: Students' response (4th, 5th and 6th year of study) to the study amounted to 71,3 %. The results showed that clinical experience and the number of correct answers from knowledge assessment increased with the year of study. Students with completed dental laboratory technician school took statistically significantly larger number of impressions and fabricated a significantly larger number of fixed restorations. Additionally, the results showed a significantly higher level of agreement with the statements about their perception of knowledge and skills. Conclusion: Students' perceptions on learning positively correlated with the number of completed semesters in prosthodontics and the students' own clinical experience.